ANALISIS DAMPAK HARGA DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN BENGKEL TOYOTA AUTO2000 SANUR - NI PUTU SYAHDA ADENIA; I WAYAN SUKARTA; COKORDA GEDE PUTRA YUDISTIRA (Universitas Mahasaraswati K. Mataram, 2024)
Development of automotive industry in Indonesian market opens up opportunities for automotive companies to enter it. This phenomenon has caused intense competition in the automotive sector, including in the workshop industry. To build a sustainable business, it is crucial for workshop industry to develop a long term relationships with customers to enhance their customer loyalty and competitive advantage. Therefore, study was conducted regarding the impact of price and service quality to customer loyalty. Population of this research is customers who use car maintenance services at the Auto2000 Sanur workshop in 2023. Sampling was conducted using purposive sampling method, concentrating on customers who do not use certain service packages. Primary data was gathered by giving questionnaires to 389 participants via social media. The data collected was studied with multiple regression using SPSS software. Findings of the research indicate that both price and service quality have a positive and significant influence to customer loyalty, both partially and simultaneously with a large influence of 86.7%, where the rest is affected by other factors that are not addressed in this study.